Hearing health of New South Wales prison inmates - Narelle Murray; Tony Butler; Eric LePage (Elsevier, 2004)
Abstract Objective: To assess the hearing health of New South Wales prison inmates. Methods: The method of testing hearing chosen was the rapid click‐evoked otoacoustic emissions technique, from which two key variables were evaluated for early status of ear damage. Hearing variables, including hearing history and self‐reported symptoms, were incorporated in a multivariate analysis of other health and demographic variables in the prison sample. Results: The analysis shows that the hearing acuity of prisoners is poor compared with the general Australian population. Variables significantly related to the hearing scores were history of hearing problems or having arthritis or diabetes. In this sample hearing did not interact with alcohol or drugs. Those testing positive for Hepatitis B Core‐Antibody were also found to have poorer hearing than those without. Conclusions and Implications:Prisoners in general have poorer hearing than a normative Australian population. Some conditions have a significant impact on hearing, which may be due to associated medications. A previous history of ear problems was found to be significantly related to hearing acuity as was a history of exposure to noise. Health screening programs within the correctional system may need to include hearing loss prevention programs and medical follow‐ups in relation to hearing health